Redefining The Term of Dukun - Sartini Sartini; Heddy Shri Ahimsa-Putra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
Dukun, wong pinter, and other terms, commonly constitutes to the term of shamanism, are often interpreted in the same way. In particular, the dukun and wong pinter are generally understood as persons who have extraordinary or even supernatural powers, are capable of communicating with spirits and understanding the unseen, can generally help resolve issues faced by members of their communities, including illnesses, spiritual disturbances, lost items, unfortunate fates, etc. They are also predicated to charge to the patient and even willing to help witchcraft to harm other people. In fact, not all shamans have negative behaviors. In Temanggung, Central Java, though this general understanding is still common, there is distinction in the specific details and characteristics of the dukun and wong pinter. Dukun are often understood negatively, meanwhile the wong pinter has more positive connotations. Because of the different principle meaning the both terms should not be generalized and used appropriately and wisely. Improper use can cause discomfort in the community, and academically the both term actually refers to a completely different subject characteristics.